Characteristics of the high temperature mechanisms of creep and recovery in graphite - College of Aeronautics, (Cranfield) (College of Aeronautics, 1962)
The research reported in this document has been made possible through the support and sponsorship of the U.S. Department of the Army, through its European Research Office. This report, not necessarily in final form, is intended only for the internal management use of the contractor and the U.S. Department of the Army.